ANALISIS PENGARUH KINERJA KEUANGAN DAN VARIABEL MAKROEKONOMI TERHADAP RETURN SAHAM SUBSEKTOR PERKEBUNAN - Faizul Mubarok; Hermanto Siregar; Nunung Nuryartono (Signifikan: Jurnal Ilmu Ekonomi, 2014)
EVA and MVA are used to indicate the creation of value in an investment. Arbitrage Pricing Theory (APT) explained that macroeconomic variables have a systematic effect on return. The aim of this study is to analyze and to measure the effect of financial performance and macroeconomic variables on the stock return of estate plantation sub-sector at Indonesia Stock Exchange. Data are processed by using panel data, analysis which consist of six companies which are listed on the estate plantation sub-sector and using quarterly data from 2007 to 2013. By using the Pooled Least Square (PLS) the result show that the variables of MVA, oil, inflation, interest rate and crisis have significant effects on the stock return of estate plantation sub-sector while the variables of MVA and the world oil price do not have significant effect on the stock return of estate plantation sub-sector.DOI: 10.15408/sjie.v3i2.2058